2022
DOI: 10.1002/ajpa.24638
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluating population histories in Patagonia and Tierra del Fuego, Chile, using ancient mitochondrial and Y‐chromosomal DNA

Abstract: Objectives: This study aims to characterize the genetic histories of ancient hunter-gatherer groups in Fuego-Patagonia (Chile) with distinct Marine, Terrestrial, and Mixed Economy subsistence strategies. Mitochondrial (mtDNA) and Y-chromosome data were generated to test three hypotheses. H 0 : All individuals were drawn from the same panmictic population; H 1 : Terrestrial groups first populated the region and gave rise to highly specialized Marine groups by $7,500 cal BP; or H 2 : Marine and Terrestrial group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 90 publications
(191 reference statements)
0
2
0
Order By: Relevance
“…In addition, the identification of these lineages has been possible only after a significant increase in the sample size and geographical coverage. The overall low uniparental genetic diversity [63,[72][73][74]76,78,99], together with the reported excess of short Runs of Homozygosity [75] and the low conditional heterozygosity [76] from genome-wide data, support a reduced effective population size. This scenario is compatible with the founder effect(s) during the peopling of the region, followed by isolation and persistent small group sizes.…”
Section: Diversification and Interactions Among Human Populations Dur...mentioning
confidence: 87%
See 2 more Smart Citations
“…In addition, the identification of these lineages has been possible only after a significant increase in the sample size and geographical coverage. The overall low uniparental genetic diversity [63,[72][73][74]76,78,99], together with the reported excess of short Runs of Homozygosity [75] and the low conditional heterozygosity [76] from genome-wide data, support a reduced effective population size. This scenario is compatible with the founder effect(s) during the peopling of the region, followed by isolation and persistent small group sizes.…”
Section: Diversification and Interactions Among Human Populations Dur...mentioning
confidence: 87%
“…Ancient DNA studies of Y-chromosome have been carried out since the early stages of genetic research in the region [72][73][74], focusing on Short Tandem Repeats (STR) and the C to T transition at the DYS199 locus as a diagnostic polymorphism of Q-M3 haplogroup (also known as Q1b1a1a (ISOGG 2019)), a widespread lineage across the Americas. In all individuals from Patagonia yielding positive results, the lineage Q-M3 has been characterised.…”
Section: First Stages Of Human Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…This lower genetic diversity could be the result of migration histories, adaptation to the environment, founder effects and/or other forms of genetic drift (Crespo et al, 2018; de la Fuente et al, 2015). In this context, recent mitochondrial DNA and Y‐chromosome results show that hunter‐gatherers represent distinct lineages that diverged before the ancestors of marine and terrestrial hunter‐gatherers migrated into SP (Balentine et al, 2023). Other genome‐wide DNA studies identified patterns that pointed to the earliest marine groups as being descendants of terrestrial groups (Nakatsuka et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Other genome‐wide DNA studies identified patterns that pointed to the earliest marine groups as being descendants of terrestrial groups (Nakatsuka et al, 2020). Genetic structure for Late Holocene SP populations identifies separated clusters for the ecogeographical regions (Balentine et al, 2023; Crespo et al, 2018; Nakatsuka et al, 2020). However, a cline was also presented ranging from SGB at one end to the people who inhabited western archipelagos at the other, a cline that is more noticeable in individuals from MP, in a middle point between NIG and BC individuals (Nakatsuka et al, 2020).…”
Section: Discussionmentioning
confidence: 99%